Hybrid Government: Mixed and Hybrid Models of Public Service Delivery in Disadvantaged, Foremost and Outermost Regions - Aripin, Sofjan; Rulinawaty, Rulinawaty (KnE Social Sciences, 2022)
The realization of public services can be hampered by a lack of resources owned by local governments. In such cases, multi-actor governance or hybrid government has been identified as a critical alternative to improve governance solutions. Hybrid government is difficult to assess. In the market economy, hybrids play a role. We find that, depending on the hybrid government model, providing alternative services in the lagged, frontier and outermost areas can result in an increase or decrease in public services in terms of distribution, procedure and legality. This research examined different types of health services, including the Covid-19 vaccine, mass circumcision, cleft lip correction, and services for stunting. The three types of justice considered were: (1) distributive justice; (2) procedural justice; and (3) recognition justice. According to the findings, the implications of health-care policy for hybrid governments are: 1) transparent decision-making regarding the distribution of costs and benefits; 2) maintain public trust; and 3) use of experts combined with local community mutual assistance to identify the current and future environment. Keywords: hybrid government, public-private partnerships, hybrid delivery, public service